Associations between food and beverage purchases and skin carotenoids among diverse small food retail store customers - Jocelyn Dixon; Virginia C Stage; Kimberly P Truesdale; Qiang Wu; Kathryn Kolasa; Lindsey Haynes-Maslow; Jared T McGuirt; Stephanie Jilcott Pitts (Cambridge University Press, 2023)
Abstract Objective: To determine if customer purchases at small food stores are associated with healthfulness of the diet as approximated by skin carotenoids. Design: This is a cross-sectional survey of customers in small food stores regarding demographics and food purchases. Food and beverage purchases were classified as 'healthy' or 'non-healthy' and 'carotenoid' v. 'non-carotenoid' using a systematic classification scheme. Fruit and vegetable intake was objectively assessed using a non-invasive device to measure skin carotenoids. Associations between variables of interest were examined using Pearson's correlation coefficients, t tests and multiple linear regression analyses. Setting: Twenty-two small food retail stores in rural (n 7 stores) and urban (n 15) areas of North Carolina. Participants: Customers of small food stores Results: Of study participants (n 1086), 55·1 % were male, 60·0 % were African American/Black and 4·2 % were Hispanic, with a mean age of 43·5 years. Overall, 36 % purchased at least one healthy item, and 7·6 % of participants purchased a carotenoid-containing food/beverage. Healthy foods and beverages purchased included produce, lean meats, 100 % juices, plain popcorn, plain nuts, milk and yogurt. Unhealthy items included non-100 % juices, crackers, chips, candy, cakes and donuts. Purchase of a healthy or carotenoid-containing item was positively associated with skin carotenoid scores (P = 0·002 and 0·006, respectively). Conclusions: A relatively small proportion of customers purchased any healthy or carotenoid-containing foods and beverages, and those who did purchase healthy options had higher skin carotenoid scores. Future research should confirm these findings in different populations.